KEBIJAKAN INDONESIA TERHADAP IMPOR SAMPAH KERTAS DARI AMERIKA SERIKAT TAHUN 2017-2019 - Eka Juwita; Pazli " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This study discusses the Indonesian state policy on paper waste imports from the United States in 2017-2019. Paper and pulp is an important industry in Indonesia and ranks ninth as the world's largest pulp producer, and sixth in the paper industry. The lack of raw materials for new paper in Indonesia encourages the import of paper waste as raw material for paper in Indonesia. In this study, data were collected from books, journals, articles, mass media and official websites. In addition, the perspective used by the author is a neoliberal perspective with foreign policy theory and the level of analysis of the nation state.Weak legal regulations regarding waste in Indonesia have a significant impact on Indonesia. The factor that causes Indonesia to import paper waste is in order to protect Indonesia's forests and the production costs incurred are considered cheaper than the production of new raw materials. Behind this cooperation between the two countries, the United States is known to have violated its cooperation agreement by smuggling B3 waste and plastic waste in containers of paper waste raw materials. The smuggling of plastic waste behind the import of paper waste is detrimental to Indonesia.The results of this study show that Indonesia's policy in overcoming the import of paper waste from the United States is by issuing a policy which includes re-exporting containers containing B3 and plastic waste, ratifying the Basel convention through presidential decree number 61 of 1993 and revising the regulation of the minister of trade No. 31/2016 be No. 84/2019. Keywords: Industry waste, smuggling of B3 waste, impact on Indonesia, Indonesian Regulation.